The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.3390/ijerph16111993
|View full text |Cite
|
Sign up to set email alerts
|

Burnout and Metabolic Syndrome in Female Nurses: An Observational Study

Abstract: Nurses are at risk of having burnout due to workload and job stress—studies have reported that chronic stress is associated with metabolic syndrome. This study aimed to assess the association between burnout and metabolic syndrome in a sample of female nurses. Data were collected from a cross-sectional study from 2016 to 2018 in a tertiary hospital in Mexico City. All nurses that work in the hospital were invited to participate. Information pertaining to sociodemographic (age, education level), work (labor sen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
52
3
3

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(65 citation statements)
references
References 41 publications
2
52
3
3
Order By: Relevance
“…Connor et al reported that a sense of professional autonomy and being fairly treated were connected to EE. Chico‐Barba et al also found a significant association between night shift and EE. It seems that favorable peer relationships and normal daily routine may help to avoid EE.…”
Section: Discussioncontrasting
confidence: 50%
“…Connor et al reported that a sense of professional autonomy and being fairly treated were connected to EE. Chico‐Barba et al also found a significant association between night shift and EE. It seems that favorable peer relationships and normal daily routine may help to avoid EE.…”
Section: Discussioncontrasting
confidence: 50%
“…This study revealed a high prevalence of BS among PHC nursing professionals, corresponding to 18.3%, with a spatial distribution ranging from 3.7% to 23.5%. Distinct results on the prevalence of BS were found among investigations involving nursing professionals from various work sectors, especially those conducted by Rossi, Santos and Passos [44], Holmes et al [45], Falgueras et al [46], Ferreira and Lucca [47], Merces et al [48], Lima et al [49], Chico-Barba et al [10], with BS prevalences of 10%, 11.1%, 9.6%, 5.9%, 58.3%, 56.6%, and 19.6%, respectively. However, the variation in prevalence in the studies cited is justified by the multiple criteria used to evaluate BS.…”
Section: Discussionmentioning
confidence: 99%
“…However, the variation in prevalence in the studies cited is justified by the multiple criteria used to evaluate BS. In this study, the criterion chosen is the most widespread in the national and international literature, as it does not overestimate BS [9,10,22,47].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations